Phân tích đồng thời các chất ô nhiễm hữu cơ trong nước lụt ở miền Trung Việt Nam - Hà, Trịnh Thu; W. Strowble, Bjarne; Trung, Nguyễn Quang; Giang, Lê Trường (Vietnam Journal of Chemistry, 2016)
The first information on organic micro-pollutants in flooding water in central Vietnam was show in this study. Flooding water samples were collected from river, canals around village, canals in rice field, and in the rice field between flooding in 2013. A comprehensive gas chromatography-mass spectrometry (GC/MS) combination of an automated identification and quantification system with database (AIQS-DB) was used to analysis flooding water sample. 284 analytes were found with concentration from 0.005-7.6 µg/l and frequently detected > 10 %. Average total concentration of group compound from household is highest, after that group compound from agriculture, and at least group compound from industry. This study indicated that flooding water was polluted by domestic chemicals from the villages and pesticides from the rice field. Keywords. AIQS-DB, organic contaminant screening, flooding water, rice field, pesticides.